Landfill odour detection using Quartz Crystal Microbalance (QCM) - Saiful Azhar, Saad; Mohd Noor, Ahmad; Siti Nordiyana, M.S. (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Odour is considered as the main environmental pollution agent in Malaysia. Eventhough the standard permitted level has not been set for Malaysia as for air and water, but still the odour has been connsidered as one of the environmental pollution as people started to concerned about the odour. Conventionally, the odour was detected by the olfactometry, which used human as its panel. But, the human panels are fatigue and aunable to produce a consistance result, especially for the continous monitoring. In this study, the quartz crystal microbalance (QCM) was used as an odour detector. The QCM is basically a mass sensitive device with the ability to measured a very small change on a quartz crystal resonator in real time. This system basically comprises of an array of sensors as well as data acquisition and components analysis. A principle component analysis (PCA) was used to define the distinct regions, according to the time of the samples being taken and hence allow the landfill odour differentiation.